Management of delayed bleeding after endoscopic mucosal resection of large colorectal polyps: a retrospective multi-center cohort study - van der Star, Simone; Moons, Leon M.G.; ter Borg, Frank; van Bergeijk, Jeroen D.; Geesing, Joost M.J.; Groen, John N.; Ouwehand, Renske J.; Vleggaar, Frank P.; de Vos tot Nederveen Cappel, Wouter H.; Wolfhagen, Frank H.J.; Schwartz, Matthijs P.; Didden, Paul (Endoscopy International Open, 2020)
Background and study aims Delayed bleeding (DB) is the most frequent major adverse event after endoscopic mucosal resection (EMR) of large non-pedunculated colorectal polyps (LNPCPs). Evidence-based guidelines for management of DB are lacking. We aimed to evaluate the clinical presentation, treatment and outcome of patients with DB and to determine factors associated with hemostatic therapy.Patients and methods Patients with DB were identified by analyzing all consecutive EMR procedures for LNPCPs (≥ 2 cm) from one academic center (2012–2017) and seven regional hospitals (2015–2017). DB was defined as any postprocedural bleeding necessitating emergency department presentation, hospitalization or reintervention. Outcome of DB was assessed for three clinical scenarios: continued bleeding (CB), spontaneous resolution without recurrent bleeding during 24 hours observation (SR), and recurrent bleeding (RB). Variables associated with hemostatic therapy were analyzed using logistic regression.Results DB occurred after 42/542 (7.7 %) EMR procedures and re-colonoscopy was performed in 30 patients (72 %). Re-colonoscopy and hemostatic therapy rates were 92 % and 75 % for CB (n = 24), 25 % and 8 % for SR (n = 12), and 83 % and 67 % for RB (n = 6), respectively. Frequent hematochezia (≥ hourly) was the only factor significantly associated with hemostatic therapy (RR 2.23, p = 0.01). Re-bleeding after endoscopic hemostatic therapy occurred in 3/22 (13.6 %) patients.Conclusion Ongoing or recurrent hematochezia is associated with a high rate of hemostatic therapy, warranting re-colonoscopy in these patients. A conservative approach is justified when bleeding spontaneously settles, and without recurrent hematochezia during 24 hours observation patients can be safely discharged without endoscopic re-examination.